2001
DOI: 10.1182/blood.v97.7.2031
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways involved in soluble fractalkine–induced monocytic cell adhesion

Abstract: Fractalkine displays features that distinguishes it from the other chemokines. In particular, besides its chemoattractant action it promotes, under physiologic flow, the rapid capture and the firm adhesion of a subset of leukocytes or intervenes in the neuron/microglia interaction. This study verified that indeed the human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 55 publications
11
72
1
1
Order By: Relevance
“…Indeed, many groups have reported that s-FKN can mediate both chemotaxis and adhesion of monocytes and THP-1 cells, whereas Pan et al (19) have reported that neither the chemokine-like domain nor the entire extracellular domain of FKN have chemotactic effects on human monocytes and THP1 cells. In our present study, we show that s-FKN, which as we have previously reported, increases adherence of monocytic MonoMac6 cells (28), fails to induce the migration of MonoMac6 cells and monocytes. Imai et al (22), who had initially reported a chemotactic effect of s-FKN, which they qualified as marginal compared with MCP-1, presented evidence in a following report (25), that, in monocytes, FKN functioned as an adhesion molecule, strengthening the interaction between monocytes and endothelial cells, rather than as a chemotactic factor.…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, many groups have reported that s-FKN can mediate both chemotaxis and adhesion of monocytes and THP-1 cells, whereas Pan et al (19) have reported that neither the chemokine-like domain nor the entire extracellular domain of FKN have chemotactic effects on human monocytes and THP1 cells. In our present study, we show that s-FKN, which as we have previously reported, increases adherence of monocytic MonoMac6 cells (28), fails to induce the migration of MonoMac6 cells and monocytes. Imai et al (22), who had initially reported a chemotactic effect of s-FKN, which they qualified as marginal compared with MCP-1, presented evidence in a following report (25), that, in monocytes, FKN functioned as an adhesion molecule, strengthening the interaction between monocytes and endothelial cells, rather than as a chemotactic factor.…”
Section: Discussionsupporting
confidence: 59%
“…Upon incubation with CX 3 CL1, the former cells showed increased phosphorylation of PI3K, Erk1/2, Akt and Src and de novo induction of p-p38 (ref. 29), similar to that reported for normal germinal center B cells. 17 Studies with specific inhibitors demonstrated that all of the above kinases were involved in CX 3 CL1-induced chemotaxis, indicating that the PI3K and Src platforms integrated signals from either scaffold.…”
Section: Discussionsupporting
confidence: 87%
“…Five purified leukemic cell suspensions that migrated to CX 3 CL1 were incubated for different times with or without CX 3 CL1 and subjected to western blot or immunoprecipitation analyses using antibodies against unphoshorylated and phosphorylated (p)-p38, Akt, Erk1 and Erk2 and Src. 29 Quantitative analysis of the bands was performed by densitometry. Akt, Erk1, Erk2, and Src, but not p38 were constitutively phosphorylated in all CLL suspensions (Figure 2a).…”
Section: Cl1-driven Signal Transduction In Cll Cellsmentioning
confidence: 99%
“…Results concerning p38 involvement differ depending on the cell and the conditions studied (32,34). The MAP kinase p38 may also be involved in adhesion through adhesion molecule up-regulation (35) and cytoskeletal remodeling (36).…”
Section: Discussionmentioning
confidence: 99%